Effectiveness of Enriched Milk with Ashwagandha Extract and Tryptophan for Improving Subjective Sleep Quality in Adults with Sleep Problems: A Randomized Double-Blind Controlled Trial - Silvia Pérez-Piñero; Juan Carlos Muñoz-Carrillo; Jon Echepare-Taberna; Macarena Muñoz-Cámara; Cristina Herrera-Fernández; Vicente Ávila-Gandía; María Heres Fernández Ladreda; Javier Menéndez Martínez; Francisco Javier López-Román (Clocks & Sleep)
A randomized, double-blind and controlled study was conducted to assess the effectiveness of the intake of 250 mL of lactose-free skimmed milk enriched with ashwagandha (Withania somnifera) alone or combined with tryptophan vs. non-enriched milk (control) on the subjective quality of sleep in healthy adults with sleep problems. The duration of supplementation was 90 days. Fifty-two eligible subjects were assigned to the study arms of ashwagandha 250 mg, ashwagandha 250 mg plus tryptophan 175 mg, ashwagandha 600 mg, and control with 13 subjects in each group. It was hypothesized that ashwagandha plus tryptophan could be superior to ashwagandha alone for improving sleep-related variables. Changes in the visual analogue scale (VAS) for sleep quality were significantly higher in the three experimental groups as compared with controls (p = 0.014). Improvements in the subscales of the Pittsburg Sleep Quality Index (PSQI) were found in all groups, but between-group differences were not significant. In the index of insomnia severity, decreases were higher in the three experimental groups as compared with controls especially in the group of ashwagandha 600 mg. Daytime somnolence was also reduced in the three experimental groups. Changes in anxiety levels and Morningness–Eveningness Questionnaire were not observed. The study products did not elicit changes in body composition and were well tolerated and safe. The data did not support the hypothesis, as the combination of ashwagandha and tryptophan did not show greater benefits in improving sleep quality than ashwagandha alone. However, the results from the three experimental groups containing ashwagandha were more favorable compared to the placebo group.